Protein Components of Bacteriophages λ and λ Virulent - Villarejo, M. (1967)
Parallel studies have been made of the protein coats of the temperate bacteriophage λ and of a deletion mutant, λ virulent. A new method for preparing ghosts of both phages by the action of Cu(++) is described. Protein ghosts of both phages can be dissolved in citrate at pH values below 3, more rapidly in the presence of 8 m urea. Both phages yielded three apparently identical protein components which can be separated by thin-layer gel filtration and thin-layer gel electrophoresis. The protein of molecular weight 47,000 ± 1,500 represents about 55% of the protein of the ghosts and is therefore likely to be the subunit of the head. The other proteins of molecular weight 30,000 ± 1,500 and 16,000 ± 1,500 represent approximately 25% and 20% of the protein, respectively. Amino acid analyses of the ghosts from the two phages have been carried out and show no significant differences. The buoyant density of phage λ virulent is 0.016 g/ml less than that of λ. Since no differences have been found in the protein components of the two phages, this indicates that the virulent mutant contains approximately 16% less deoxyribonucleic acid than the temperate phage.